Emerging urban housing markets: a tale of two cities - TSENKOVA, Sasha (European Spatial Research and Policy, 1999)
The paper conceptualises the process of transition from a centrally planned to a market-based housing system focusing on processes of change in the emerging home ownership markets. The Bulgarian housing situation, given the legacy of 90% home ownership, offers both opportunities and challenges as a setting for a case study. On the one hand, it enables the observation of typical processes associated with the transition to market economy in Central and Eastern Europe: privatisation, changes in housing finance, restructuring of housing production, and emerging residential differentiation. On the other hand, it provides a revealing variation in the process of change as il is experienced in local markets. The research evaluates the impact of housing reforms on the production, distribution and consumption of owner-occupied housing in Bułgaria. A set of key linkages relates the economy, the housing market and the behaviour of market-based institutions and actors in the provision system. The analysis explores those linkages in two buoyant local markets focusing on house price dynamics, market differentiation and demand-driven changes in the supply of owner-occupied housing.